La Cerámica Ática y su Historiografía - Diana Rodríguez Pérez (Classica Digitalia: Classica Instrumenta, 2019)
History of Athenian figure-decorated pottery from the 6th to the 4th centuries BC, touching on technological aspects and iconography as well as on the find contexts of the vases. It also showcases current and past approaches to the study of Athenian pottery, making special emphasis on the figure of Sir John Beazley, the Oxford Professor who contributed to shape the discipline.